Lee et al. Trends in Metabolic Syndrome Severity and Lifestyle Factors Among Adolescents. Pediatrics. 2016;137(3);doi:10.1542/peds.2015-3177 (Pediatrics, 2016)
Unaccompanied migrant children and families seeking humanitarian protection face health and well-being risks throughout the migration journey. US immigration policies and enforcement practices that subject children and families to detention and separation compound these risks. Grounded in the Best Interest of the Child (BIOTC) framework, this policy statement recontextualizes reception and proposes recommendations to ensure the safety and well-being of children and families seeking humanitarian protection.